2020
DOI: 10.7717/peerj.8830
|View full text |Cite
|
Sign up to set email alerts
|

Icariin affects cell cycle progression and proliferation of human retinal pigment epithelial cells via enhancing expression of H19

Abstract: Background Aberrant proliferation of retinal pigment epithelial (RPE) cells under pathologic condition results in the occurrence of proliferative vitreoretinopathy (PVR). Icariin (ICA)-a flavonol glucoside-has been shown to inhibit proliferation of many cell types, but the effect on RPE cells is unknown. This study aimed to clarify the inhibitory effects of ICA on RPE cells against platelet-derived growth factor (PDGF)-BB-induced cell proliferation, and discuss the regulatory function of H19 in RPE cells. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…This is evidenced by the upregulation of key enzymes such as 5-LO, HAase, MPO, and NOX2, which are involved in the production of in ammatory eicosanoids such as prostaglandins, thromboxanes, and leukotrienes from arachidonic acid, TNFα, IL-1β, IL-6, and IL-10. Previous studies [44][45][46][47] have reported that 5-LO is responsible for the production of mediators of in ammatory reactions, and its inhibition represents a promising target for the treatment of various in ammatory pathologies. Our ndings are consistent with the work of Vilas-Boas et al [43], who reported that NADPH oxidase inhibition improves β-cell function and viability.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the upregulation of key enzymes such as 5-LO, HAase, MPO, and NOX2, which are involved in the production of in ammatory eicosanoids such as prostaglandins, thromboxanes, and leukotrienes from arachidonic acid, TNFα, IL-1β, IL-6, and IL-10. Previous studies [44][45][46][47] have reported that 5-LO is responsible for the production of mediators of in ammatory reactions, and its inhibition represents a promising target for the treatment of various in ammatory pathologies. Our ndings are consistent with the work of Vilas-Boas et al [43], who reported that NADPH oxidase inhibition improves β-cell function and viability.…”
Section: Discussionmentioning
confidence: 99%